(untitled) (AYUSHDHARA, 2016)
Yoni Vyapad is a compilation of various disorders of the genital tract ranging from vulva till the uterus. Local infectious conditions like vulvo vaginitis, pelvic inflammatory diseases have also been described. Among the various treatment modalities described for Yoni Vyapad, the emphasis given to Sthanika Chikitsa is noteworthy. The mode of approach through local route (with or without oral treatment) is with the aim to give instantaneous relief to the suffering woman. Pichu Prayoga is one such intervention among which “Shatavari ghrita pichu” has been specifically mentioned in the context of Pittaja Yoni Vyapad. The symptoms which are seen in the stubborn vulvo vaginitis conditions need effective treatment procedures. The use of a topical medicine like Pichu will act directly on the vaginal mucosa and enable easier and target specific action. Therefore it helps to combat the local disease causing agent and simultaneously strengthen the vagina as well as prevent recurrence. Simultaneous oral ingestion of the drug alongside, takes care of the complete eradication and relief of the disease symptoms. Since Ghrita is the best Pitta Shamaka, Shatavari Ghrita is chosen for our study in Pittaj Yonivyapad which is a Pitta pradhan vyadhi seen frequently these days. A Clinical Trial was carried out on 60 patients detected with Pittaj Yonivyapad with a trial group of 30 patients undergoing oral treatment of Shatavari Ghrita orally and Shatavari Ghrita Pichu vaginaly for 7 days in comparison with same number of patients taking oral tablets of Clindamycin with Clindamycin pessaries kept vaginally for equal number of days. The drugs were prepared in the College Pharmacy and the Research conducted in the PTSR OPD of Loknete Rajaram Bapu Ayurvedic College, Hospital and PG Institute, of which we got satisfactory results of 50 – 75% in comparison with the allopathic drugs for Pelvic Inflammatory Disease.